A PROSPECTIVE STUDY TO COMPARE THE POST-OPERATIVE PAIN AND POST-OPERATIVE COMPLICATIONS IN CONVENTIONAL GRID IRON AND TRANSVERSE CREASE COSMETIC INCISION APPENDECTOMY - Singh, Ramandeep; Salim, Mohammed; Jalthania, Mahendra Kumar; Yadav, Vijay Kumar (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: The objective of our study is to compare the conventional grid iron incision with transverse crease cosmetic incision in terms of post-operative pain, mean operating time, duration of hospital stay, and post-operative complications. Methods: This is a prospective and comparative study and was carried out between December 2021 and November 2022. During the study period, 50 patients presented to surgical outdoor and emergency at PBM hospital, Bikaner, with clinical presentation and eventual radiological diagnosis of acute appendicitis were enrolled in the study and were randomly allocated to two groups including grid iron=25 and transverse crease=25. All patients were contacted 1 week and 2 months after surgery and the efficacy of grid iron and transverse crease incision in terms of post-operative pain, mean operating time, duration of stay in hospital, and post-operative complications. Results: Post-operative pain, duration of stay in hospital (mean stay for grid iron group=4.32 vs. transverse crease group=2.16 days), and operating time (mean operating time for grid iron group=33 min vs. transverse crease group was 20.3 min) were significantly lower in cases of transverse crease incision as compared to grid iron cases. Post=operative complications were lesser in transverse crease incision but were not very significant as compared to grid iron incision. Conclusion: Open appendectomy using transverse crease cosmetic incision was superior to conventional grid iron incision in terms of post-operative pain, operating time, duration of hospital stay, blood loss, and post-operative complications.